Hudson Bay : or, Everyday life in the wilds of North America : during six years' residence in the territories of the Hon. Hudson Bay Company - Ballantyne, R. M. (Robert Michael), 1825-1894. (London, 1886)
1st edition, Edinburgh, 1848. Added t.-p. with vignette. Mode of access: Internet.